Vocational education for American youth (Distributed by ERIC Clearinghouse, 1964)
Education for living and education for earning a living must be regarded as integral parts of a comprehensive program fitting American youth for their future responsibilities. In this country, vocational education serves two major functions--(1) it provides the opportunity for secondary school youth to acquire, along with or following a general education, some type of specific and useful occupational training, and (2) it provides a very important continuing program of training for out-of-school youth and adults who want and can profit from extended skills, knowledge, and understandings in a chosen occupation. This booklet, concerned only with the first function, briefly describes the philosophy underlying vocational education, points out some of the essential features of a sound vocational program, and indicates the contributions this specific education makes to the nation's security and prosperity. (sl)